Identifying keys to win in the World Karate Championship - Seyedi, R.; Zhong, Y.; Khodaparast, S.; Sigillo, D.; Azizi, A.; Qu, Y. (Annals of Applied Sport Science, 2020)
Background. Studies in this domain help focus on the techniques with high application to improve the point attainment, without providing points for the other opponents. Objectives. The purpose of this study was to analyze and investigate the most common scoring techniques used and the highest intensity competition times that have been fulfilled by the champions of the World Karate Leagues 2019 and the World Championship 2018. Methods. One hundred and eighteen karate competitions in 5 weight groups (-60, -67, -75, -84, and +84) and from each weight rank, including 5 top-level athletes of the World Karate Federation ranking, were analyzed and studied. This study data were collated using Video Analyzer, Microsoft Excel, and SPSS, and the data were assessed using the Chi-square statistical tests (?2). Results. This study indicated that only 31.9% of total attacks fulfilled by the world champions were successful in gaining points, the last minute of competition was the highest intensity time in a three-minute competition (with 46.70% of attacks happening then), and the techniques of Ashi Barai and Gia Kuzuki were the most commonly used techniques among the techniques for scoring used by world champions. Conclusion. The coaches must develop new strategies during the training sessions and compare their athletes` techniques with those of the world elites to gain uniform endeavors and improve their athletes` performance to reach the level of world champions